X Inactivation and Escape: Epigenetic and Structural Features - Fang, He; Disteche, Christine M.; Berletch, Joel B. (Frontiers in Cell and Developmental Biology, 2019)
X inactivation represents a complex multi-layer epigenetic mechanism that profoundly modifies chromatin composition and structure of one X chromosome in females. The heterochromatic inactive X chromosome adopts a unique 3D bipartite structure and a location close to the nuclear periphery or the nucleolus. X-linked lncRNA loci and their transcripts play important roles in the recruitment of proteins that catalyze chromatin and DNA modifications for silencing, as well as in the control of chromatin condensation and location of the inactive X chromosome. A subset of genes escapes X inactivation, raising questions about mechanisms that preserve their expression despite being embedded within heterochromatin. Escape gene expression differs between males and females, which can lead to physiological sex differences. We review recent studies that emphasize challenges in understanding the role of lncRNAs in the control of epigenetic modifications, structural features and nuclear positioning of the inactive X chromosome. Second, we highlight new findings about the distribution of genes that escape X inactivation based on single cell studies, and discuss the roles of escape genes in eliciting sex differences in health and disease.